Curiosités géographiques et missions jésuites en Asie du Sud-est dans la première moitié du XVIIe siècle : La Descripsão do Reyno dos Laos, e dos circumvizinhos a ella - Dejanirah Couto (Etudes Epistémè, 2014)
The present article contextualizes and examines a cartographic sketch of the kingdom of Laos and its neighbours, preserved in the Biblioteca do Palacio Real de Ajuda of Lisbon, in the manuscript Jesuitas na Asia, 49-V-32, fol.85. Although widely unnoticed, this drawing of Laos of 30x22cm, dated probably 1642/1643, constitutes a rarity, because we don’t have at our disposal many sketches, illustrations or plans which can be attributed to the Jesuits, in particular in Asia and in the 17th century. The sketch, a testimony of Jesuit curiosity tinged with pragmatism, according to the orientation of the Society of Jesus in the context of the Counter-Reformation, was executed maybe by Father Giovanni Maria Leria, and it reflects the political and economic strategies of the Society. This one tried to establish a mission in Laos in order to open a “missionary road” east of Tonkin, heading to the Chinese border, far from the Middle Kingdom coast and the Japanese archipelago, where a succession of political, religious and military events created serious problems to the Society of Jesus at the beginning of the 17th century, and forced it to rethink the strategies of setting up in South-East Asia. Established in the shadow of the Tonkin mission, which benefited itself from the economic support of the Japanese Diaspora in Indochina (formed partially by Christians), the mission of Laos suffered from the kingdom isolation, its bad relations with Siam and also from the war involving its two neighbours of the Peninsula, the Trinh in the Nord and the Nguyên in the South. To protect the mission, the Jesuits promised to king of Laos the opening of relations with Macao, expected to supply the kingdom with weapons and goods. However, in spite of all Jesuit efforts, the mission of Laos decayed and was closed in 1650. We have, as a cartographic account of this spiritual and material adventure, the sketch of Laos, a Jesuit reading of the field in Asia in the 17th century, where one finds, entangled in a strangely tightened weft, political realism and missionary enthusiasm, economic appetites, erudite knowledge and geographical curiosities.